2003
DOI: 10.1038/sj.modpathol.3800015
|View full text |Cite
|
Sign up to set email alerts
|

Gastric PDX-1 expression in pancreatic metaplasia and endocrine cell hyperplasia in atrophic corpus gastritis

Abstract: The homeodomain transcription factor PDX-1 plays a key role in endocrine and exocrine differentiation processes of the pancreas. PDX-1 is also essential for differentiation of endocrine cells in the gastric antrum. The role of PDX-1 in the pathogenesis of endocrine cell hyperplasia and pancreatic metaplasia in corpus and fundus gastritis has not been evaluated. By immunohistochemistry and double-immunofluorescence, we investigated the expression of PDX-1 in 10 tissue specimens with normal human gastric mucosa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…An opposite view has been mentioned in one study in which PDX-1 was considered as a tumor suppressor gene in human gastric cancer 45. Further studies are needed to clarify this issue, since most studies showed high level of PDX-1 in gastric cancer specimens4650, as opposite to this study showing low expression of PDX-1 in a single human gastric cancer cell line.…”
Section: Discussioncontrasting
confidence: 84%
“…An opposite view has been mentioned in one study in which PDX-1 was considered as a tumor suppressor gene in human gastric cancer 45. Further studies are needed to clarify this issue, since most studies showed high level of PDX-1 in gastric cancer specimens4650, as opposite to this study showing low expression of PDX-1 in a single human gastric cancer cell line.…”
Section: Discussioncontrasting
confidence: 84%
“…Shh is normally found at high levels in the proximal corpus of the human stomach. Its expression is lost in atrophic gastritis 61 and IM, 62 with lower expression levels being observed in incomplete versus the complete subtype 38 . Loss of shh is an early change in premalignant lesions which may also contribute to gastric cancer, although this may be due to its expression in parietal cells which are lost along the progression from atrophy to gastric cancer.…”
Section: Is Intestinal Metaplasia a Premalignant Condition?mentioning
confidence: 99%
“…Expression of PDX-1 has been reported in pancreatic metaplasia of the stomach in humans. 2,8 No positive reaction was observed in the pancreatic metaplasia of the stomach in the WTC-dfk rats by using immunohistochemical examination for PDX-1.…”
Section: Resultsmentioning
confidence: 90%